Utilization of healthcare services in postpartum women in the Philippines who delivered at home and the effects on their health: a cross-sectional analytical study - Yamashita T; Reyes Tuliao MT; Concel Meana M; Suplido SA; Llave CL; Tanaka Y; Matsuo H (Dove Medical Press, 2017)
Tadashi Yamashita,1 Maria Teresa Reyes Tuliao,2 Magdalena Concel Meana,2 Sherri Ann Suplido,3 Cecilia L Llave,4 Yuko Tanaka,5 Hiroya Matsuo6 1Kobe City College of Nursing, Kobe, Japan; 2Health Department of Muntinlupa, Muntinlupa, Philippines; 3Department of Obstetrics and Gynecology, Philippine General Hospital, Manila, Philippines; 4College of Medicine (CM), University of the Philippine (UP), Manila, Philippines; 5Department of School of Health Sciences, Faculty of Medicine, Tokushima University Graduate School, Tokushima, Japan; 6Department of International Health, Kobe University Graduate School of Health Sciences, Kobe, Japan Background: A low ratio of utilization of healthcare services in postpartum women may contribute to maternal deaths during the postpartum period. The maternal mortality ratio is high in the Philippines. The aim of this study was to examine the current utilization of healthcare services and the effects on the health of women in the Philippines who delivered at home. Methods: This was a cross-sectional analytical study, based on a self-administrated questionnaire, conducted from March 2015 to February 2016 in Muntinlupa, Philippines. Sixty-three postpartum women who delivered at home or at a facility were enrolled for this study. A questionnaire containing questions regarding characteristics, utilization of healthcare services, and abnormal symptoms during postpartum period was administered. To analyze the questionnaire data, the sample was divided into delivery at home and delivery at a facility. Chi-square test, Fisher’s exact test, and Mann–Whitney U test were used. Results: There were significant differences in the type of birth attendant, area of residence, monthly income, and maternal and child health book usage between women who delivered at home and those who delivered at a facility (P<0.01). There was significant difference in the utilization of antenatal checkup (P<0.01) during pregnancy, whilst there was no significant difference in utilization of healthcare services during the postpartum period. Women who delivered at home were more likely to experience feeling of irritated eyes and headaches, and continuous abdominal pain (P<0.05). Conclusion: Financial and environmental barriers might hinder the utilization of healthcare services by women who deliver at home in the Philippines. Low utilization of healthcare services in women who deliver at home might result in more frequent abnormal symptoms during postpartum. Keywords: Philippines, health care services, postpartum, delivery at home, danger signs, abnormal symptoms